Pengembangan Desain Konseling Berbasis Pesantren dengan Pendekatan Service-Learning - Arifin, Samsul; Mufaridah, Hanik (Jurusan Bimbingan dan Konseling Islam, 2018)
Ustadh muhtasib (counselors) in the pesantren have a desire to practice counseling services that are based on their traditions but have difficulties in formulating them. The campus also has a desire to look for local wisdom-based counseling design models. Finally they reached a meeting point in community service with the service-learning method. The aim of this program is to excavate and formulate a pesantren-based local tradition-based counseling design model with the Ustadz Muhtasib community. Results: boarding-based counseling emphasizes balance (at-tawazun) starting from the philosophical side to praxis. Among other things, in view of humans as beings who have balance (at-tawazun) between leaders in the way of God (as embodiments of ‘abd Allah) and leaders in fighting for civilization and prosperity with the community (as embodiments of the Caliph of Allah). The purpose of counseling contains a balance (at-tawazun) between inviting goodness and preventing evil and the balance of the goodness of present life (ad-dunya hasanah) and the goodness of life later (al-akhirah hasanah). Characteristics of the counselor's personality, the existence of at-tawazun (balance) between shalahiyyah (capability) and shalih (integrity). Thus pesantren-based counseling, containing at-tawazun values; balance and harmony. At-tawazun is one of the characteristics of Islamic boarding schools in diversity and society that contain balance and propocial.